2007
DOI: 10.1007/s00213-007-0723-1
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortical alpha1 adrenoreceptor modulation of the nucleus accumbens dopamine response to stress in Long–Evans rats

Abstract: These data indicate that stress-induced activation of subcortical DA transmission is modulated by the NE input to PFC acting at alpha(1) receptors. They suggest that, under normal circumstances, this system exerts a facilitatory or enabling influence on the NAcc DA stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Depletion of noradrenergic and dopaminergic fibres in the PFC produced comparable dopamine efflux in depleted and control animals following exposure to stress, while sparing noradrenergic fibres and depleting dopaminergic fibres in the PFC resulted in decreased prefrontal cortical dopamine efflux in lesioned rats compared to controls following exposure to stress (Venator et al 1999). In addition, both dopamine and noradrenaline neurotransmission in the PFC has been shown to modulate subcortical dopaminergic activity (Darracq et al 1998 ;McKittrick & Abercrombie, 2007 ;Nicniocaill & Gratton, 2007 ;Pascucci et al 2007 ;Tassin, 1998 ;Ventura et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of noradrenergic and dopaminergic fibres in the PFC produced comparable dopamine efflux in depleted and control animals following exposure to stress, while sparing noradrenergic fibres and depleting dopaminergic fibres in the PFC resulted in decreased prefrontal cortical dopamine efflux in lesioned rats compared to controls following exposure to stress (Venator et al 1999). In addition, both dopamine and noradrenaline neurotransmission in the PFC has been shown to modulate subcortical dopaminergic activity (Darracq et al 1998 ;McKittrick & Abercrombie, 2007 ;Nicniocaill & Gratton, 2007 ;Pascucci et al 2007 ;Tassin, 1998 ;Ventura et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…found that the novel and unescapable/uncontrollable stressor initially induced an increase in tonic levels of DA in NAc and then led to a decrease in DA level in NAc even below prestress levels which lasted as long as the stressful situation (Nicniocaill & Gratton, 2007; Pascucci, Ventura, Latagliata, Cabib, & Puglisi‐Allegra,2007; Ventura, Cabib, & Puglisi‐Allegra, 2002). This different response corresponds with the process of the primary and secondary appraisal of a stressor which cannot be removed, escaped, or predicted by the organism, and NAc DA fluctuations are modulated by the medial prefrontal cortex, which is also involved in stress appraisal (Pascucci et al.,2007).…”
Section: Discussionmentioning
confidence: 99%
“…This was done by two independent laboratories and published in 2007. These studies showed that novel stressful experiences enhance DA release in the NAc through activation of prefrontal cortical alpha-1 adrenergic receptors (ARs) by high levels of released NE (Nicniocaill and Gratton, 2007; Pascucci et al, 2007). Indeed, the experience with a novel stressor promotes a rapid, massive, and transient increase in NE release within the mpFC which parallels the enhancement of mesoaccumbens DA release (Pascucci et al, 2007).…”
Section: Prefrontal-accumbal Catecholamine Systemmentioning
confidence: 99%
“…A selective depletion of prefrontal cortical NE prevents both the cortical NE response and the increase in accumbal DA, leaving stress-induced enhancement of prefrontal cortical DA release as well as basal CAs levels unaffected (Pascucci et al, 2007). Moreover, applications of the alpha-1 AR selective antagonist benoxathian into the mpFC inhibits stress-induced DA release in the NAc dose-dependently (Nicniocaill and Gratton, 2007). Pascucci et al (2007) also confirmed that stress-induced enhanced NAc DA release is constrained by activation of mpFC DA.…”
Section: Prefrontal-accumbal Catecholamine Systemmentioning
confidence: 99%